2013
DOI: 10.1007/s11199-013-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Threats to Feminist Identity and Reactions to Gender Discrimination

Abstract: The aim of this research was to examine conditions that modify feminists’ support for women as targets of gender discrimination. In an experimental study we tested a hypothesis that threatened feminist identity will lead to greater differentiation between feminists and conservative women as victims of discrimination and, in turn, a decrease in support for non-feminist victims. The study was conducted among 96 young Polish female professionals and graduate students from Gender Studies programs in Warsaw who sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
0
10
2
Order By: Relevance
“…For instance, they may disavow feminine beauty ideals because they perceive them as contributing to women's objectification (Murnen and Smolak, 2009 ). It is important to note that even though “distinctive feminists” do not identify highly with women, this does not mean that they are “anti-women” (see Becker et al, 2011 ; Cichocka et al, 2013 ). Rather, they disavow the (current) social construction of the group.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they may disavow feminine beauty ideals because they perceive them as contributing to women's objectification (Murnen and Smolak, 2009 ). It is important to note that even though “distinctive feminists” do not identify highly with women, this does not mean that they are “anti-women” (see Becker et al, 2011 ; Cichocka et al, 2013 ). Rather, they disavow the (current) social construction of the group.…”
Section: Discussionmentioning
confidence: 99%
“…While feminism can be conceptualised as a theoretical or political position, it has also been argued to be an identity. Cichocka, De Zavala, Kofta, and Rozum (2013) have suggested that feminism can be seen as an identity, specifically a collective political identity. However, there remains little understanding of how a political identity such as feminist may intersect with other forms of identity such as gender, which are more traditionally researched within intersectionality work.…”
Section: Intersectionalitymentioning
confidence: 99%
“…In some cases, there was a trend for there to be higher hostility displayed toward traditional targets the less sexist participants were, but these trends were not statistically significant. These results are inconsistent with Cichocka et al (2013) who found that self-identified feminists who experienced social identity threat were less sympathetic toward conservative (versus feminist) women who were the targets of discrimination.…”
Section: Replicating the Sexism-subtyping Relationshipcontrasting
confidence: 86%
“…First, participants' behavioural intentions toward the target were the primary measure of intra-gender hostility, but there are more subtle ways that intra-gender hostility may be expressed. As Cichocka et al (2013) evidenced, feminists can demonstrate less sympathy and concern for traditional women when they experience social identity threat. It may be that non-traditional women do not, or do not want to, commit overt acts of intragender hostility against other women, like public disparagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation